Prevalence and Genetic Characterization of Two Mitochondrial Gene Sequences of Strobilocercus Fasciolaris in the Livers of Brown Rats (Rattus norvegicus) in Heilongjiang Province in Northeastern China - Zhao, Fengnian; Zhou, Yun; Wu, Yanchen; Zhou, Kexin; Liu, Aiqin; Yang, Fengkun; Zhang, Weizhe (Frontiers in Cellular and Infection Microbiology, 2020)
Rodents constitute the largest and most successful group of mammals worldwide. Brown rats (Rattus norvegicus) are one of the most common rodent species as intermediate hosts of Hydatigera taeniaeformis. Although there have been a few studies reporting the presence of strobilocercus fasciolaris in brown rats worldwide, little information is available on genetic characterization of this parasite with no molecular data in China. Therefore, during a period of April 2014 to March 2016, a study was carried out to understand the prevalence and genetic characterization of strobilocercus fasciolaris in brown rats captured from northeastern China’s Heilongjiang Province. The livers of brown rats were collected, and examined for the presence of the cysts. Each cyst was identified based on morphological observation: the larvae by the naked eye and the scolexes under microscopy, and confirmed by Polymerase Chain Reaction (PCR) and sequencing of cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 4 (nad4) genes. 11.8% (13/110) of brown rats were infected with strobilocercus fasciolaris in the investigated areas. By sequence analysis, ten and six haplotypes were obtained at the cox1 and the nad4 loci, respectively with the polymorphic sites (degree of intraspecific variation): 24 (0.3–4.4%) and 42 (0.6–4.7%). A total of 12 nucleotide sequences (six at the cox1 locus and six at the nad4 locus) were not described previously. Among them, base differences in three of six novel cox1 gene sequences and five of six novel nad4 gene sequences caused amino acid changes. Phylogenetic analyses based on neighbor-joining and Bayesian inference trees of the cox1 and nad4 gene sequences indicated that all the strobilocercus fasciolaris isolates belonged to Hydatigera taeniaeformis sensu stricto (s.s.). This is the first report of the genetic characterization of strobilocercus fasciolaris in brown rats in China. The finding of the novel nucleotide and amino acid sequences of the cox1 and nad4 possibly reflects the endemic genetic characterization of this parasite. The data will be useful to explore the biological and epidemiological significance of the intraspecific variation within H. taeniaeformis s.s..